Use of the arbuscular mycorrhizal fungus Glomus intraradices as biological control agent of the nematode Nacobbus aberrans parasitizing tomato - Marro, Nicolás Alejandro (2014)
The plant-parasitic nematode Nacobbus aberrans is an endoparasite that induces gall formation in the roots and causes severe losses to diverse crops. Some populations of this nematode show preference for certain hosts, revealing the existence of "races/groups" with different behaviour and making nematode management difficult. A possible biological control alternative to reduce the damage caused by this species may be the use of arbuscular mycorrhizal fungi (AMF). In the present work, the effect of Glomus intraradices on tomato plants inoculated with the nematode at transplanting and three weeks later was tested. At 60 days, the following parameters were estimated: percentage of AMF colonization, root and aerial dry weight, number of galls and egg masses, and reproduction factor (RF=final population/initial population) of N. aberrans. AMF colonization was higher in the presence of the nematode. The use of AMF favoured tomato biomass and reduced the number of galls and RF on the plants inoculated with the nematode at transplanting.